The impact of universities on regional innovation: A critique and policy implications - Elvira Uyarra (The University of Manchester, Manchester Business School, 2008)
The impact of universities on the economic wellbeing and innovative potential of regions has been the object of intense scholarly and policy interest in the last years. Despite this interest, a clear picture is missing in relation to the roles universities are seen to play, the benefits of HEI activities and the mechanisms through which they occur. This paper proposes a review and a critique of current views on the role of universities and their associated policy implications. This paper argues that the literature provides a fragmented account of HEIs regional engagement and highlights the need for an integrated approach combining firm-level considerations, with institutional and strategic issues affecting universities engagement, and regional specific determinants shaping localised interactions.
Keywords: 330; HEIs; regional development; regional innovation systems; knowledge spillovers; entrepreneurship; knowledge transfer; university industry links; Hochschule; Hochschulforschung; Wissenstransfer; Entrepreneurship-Ansatz; Regionale Entwicklung; Korrelation